Danos socioambientais originados pelas usinas eólicas nos campos de dunas do Nordeste brasileiro e critérios para definição de alternativas locacionais - Antonio Jeovah de Andrade Meireles (Confins)
The wind potential in Brazil is an important alternative for the production of renewable energy, reducing the emission of air pollutants with the use of clean energy. An environmental policy to minimize the consequences of global warming. This article evaluated the environmental impacts of wind farms on the dune fields and changes in the geomorphological dynamics of the coastal zone. We analyzed the cumulative impacts taking as example the coast of Ceará State, defined locational alternatives and coastal environments for the generation of clean energy.